Ex Situ Conservation of Plant Genetic Resources: Global Development and Environmental Concerns - Cohen, Joel I. (American Association for the Advancement of Science, 1991)
Conservation of plant genetic resources is achieved by protection of populations in nature (in situ) or by preservation of samples in gene banks (ex situ). The latter are essential for users of germplasm who need ready access. Ex situ conservation also acts as a back-up for certain segments of diversity that might otherwise be lost in nature and in human-dominated ecosystems. The two methods are complementary, yet better understanding of this interrelation and the role of ex situ conservation in global environmental considerations is needed. Inclusion of ex situ conservation efforts within current environmental policies conserving global diversity would focus greater international attention on the safeguarding of these efforts.